The cloud searchers - Kibuishi, Kazu, 1978- (Kibuishi, Kazu, 1978- Amulet, 2010)
Emily, Navin and their crew of resistance fighters charter an airship and set off in search of the lost city of Cielis. there they hope to find held from the Guardian Council's powerful Stonekeepers. It's a mission that Alledia's survival depends on, and time is running out -- Emily's got to find Cielis before the Elf King finds her.